Antifungal effect and some properties of cell-free supernatants of two Bacillus subtilis isolates against Fusarium verticillioides - Melissa Tiemi Hirozawa; Mario Augusto Ono; Igor Massahiro de Souza Suguiura; Jaqueline Gozzi Bordini; Elisa Yoko Hirooka; Elisabete Yurie Sataque Ono (Brazilian Journal of Microbiology, 2024)

Limosilactobacillus reuteri as sustainable biological control agent against toxigenic Fusarium verticillioides - Melissa Tiemi Hirozawa; Mario Augusto Ono; Igor Massahiro de Souza Suguiura; Sandra Garcia; Jaqueline Gozzi Bordini; Ismael Rodrigues Amador; Elisa Yoko Hirooka; Elisabete Yurie Sataque Ono (Brazilian Journal of Microbiology, 2023)

Guidelines on reporting treatment conditions for emerging technologies in food processing - Vicente M. Gómez-López; Gianpiero Pataro; Brijesh Tiwari; Mario Gozzi; María Ángela A. Meireles; Shaojin Wang; Buenaventura Guamis; Zhongli Pan; Hosahalli Ramaswamy; Sudhir Sastry; Florent Kuntz; Patrick J. Cullen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Transgenic versus conventional corn: fate of fumonisins during industrial dry milling - Jaqueline Gozzi Bordini; Mario Augusto Ono; Glauco Tironi Garcia; Édio Vizoni; Ismael Rodrigues Amador; Melissa Tiemi Hirozawa; Elisabete Yurie Sataque Ono (Mycotoxin Research, 2019)

Assessment of exposure of broiler chicken in Brazil to mycotoxins through naturally contaminated feed - Carolina Nachi Rossi; Cássia Reika Takabayashi; Mario Augusto Ono; Jaqueline Gozzi Bordini; Osamu Kawamura; Edio Vizoni; Elisa Yoko Hirooka; Elisabete Yurie Sataque Ono (Food Security, 2013)